The seasonal influence of large aquatic plants at contrasting study sites on the River Frome, Dorset - Watson, Kelly Joanne (2007)
This thesis utilised the River Frome, Dorset, as a study catchment within which to examine the seasonal effects of large aquatic plants, or 'macrophytes', on hydraulic roughness, water velocity, river stage and fine sediment distribution. The thesis formed part of LOCAR, a NERC thematic research programme, and was motivated by the need to provide empirical data to improve river management and to help achieve a compromise between vegetation management for flood control and for maintaining and maximising biodiversity.